Antioxidant Enzyme Activity and Lipid Peroxidation in Aporrectodea caliginosa Earthworms Exposed to Silver Nanoparticles and Silver Nitrate in Spiked Soil. (7th May 2020) - Saleeb, Nadir; Robinson, Brett; Cavanagh, Jo; Ross, James; Munir, Kiran; Gooneratne, Ravi
Abstract: Silver nanoparticles (AgNPs) from industrial use, discharged via the land application of sewage sludge, are interacting with soil biota, including earthworms. In affected organisms, excessive production of reactive oxygen species can result in lipid peroxidation, shifting the balance between oxidants and antioxidants to cause oxidative stress. We determined selected lower‐tier biomarkers such as antioxidant responses and lipid peroxidation in Aporrectodea caliginosa earthworms exposed to soils spiked with AgNPs or silver nitrate (AgNO3 ). Aporrectodea caliginosa were exposed to AgNPs at 0 (control), 0.3, 3, 30, and 300 mg/kg or Ag + (as AgNO3 ) at 0, 0.03, 0.3, 3, and 10 mg/kg in soil for 4 wk. At 1, 2, 3, and 4 wk, the activity of the antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, glutathione S ‐transferase, as well as lipid peroxidation (malondialdehyde content), increased as a function of concentration, with a much larger response for Ag + than AgNPs. Given the likelihood of ever‐increasing AgNP concentrations in soil, where AgNPs can transform to ionic Ag (Ag + ), our findings of antioxidant response to oxidative stress in a common indicator organism even at an environmentally realistic exposure concentration of 0.03 mg/kg demonstrate that AgNPs may affect soil fertility and, thus, agricultural production. Evaluating selected lower‐tier biomarkers offers a meaningful assessment of AgNPs and Ag + effects on terrestrial earthworms. Environ Toxicol Chem 2020;39:1257–1266. © 2020 SETAC